Environment-friendly nitrogen management practices in wetland paddy cultivation - Alam, Mohammad Saiful; Khanam, Mariam; Rahman, Md. Mizanur (Frontiers in Sustainable Food Systems, 2023)
A large amount of nitrogen (N) fertilizer is required for paddy cultivation. But N use efficiency (NUE) in paddy farming is low (20-40%). Much of the unutilized N potentially degrades the quality of soil, water and air, and disintegrates the functions of different ecosystems. It is a great challenge to increase NUE and sustain rice production to meet the food demand of the growing population. This review attempted to find out promising N management practices that might increase NUE, while reducing the tradeoffs between rice production and environmental pollution. We collected and collated information on N management practices and associated barriers. A set of existing soil, crop and fertilizer management strategies can be suggested for increasing NUE which, however, might not be capable to halve N waste by 2030 as stated in the ‘Colombo Declaration’ by United Nations Environment Programme. Therefore, more efficient N management tools yet to be developed through research and extension. Awareness raising campaign among farmers is a must against their misunderstanding of higher N fertilizer provides higher yields. The findings might help the policy makers to formulate suitable policies regarding eco-friendly N management strategies for wetland paddy cultivation and to ensure better utilization of costly N fertilizer.